PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA KOPERASI SIMPAN PINJAM MULTI NIAGA MAKASSAR - Maryadi Maryadi (AkMen JURNAL ILMIAH, 2012)
Customer satisfaction is a condition in which the desires, expectations and customer requirements are met. A service rated satisfactory if the service can meet the needs and expectations of customers. Measuring customer satisfaction is a key element in delivering a better, more efficient and more effective. If customers are not satisfied with the services provided, the service can certainly be ineffective and inefficient. Quality of service can be considered as fulfilling the needs and desires of consumers and accuracy of delivery to consumer expectations mengembangi